EFEKTIVITAS PENGGUNAAN SCIENTIFIC APPROACH (PENDEKATAN SAINTIFIK) TERHADAP MOTIVASI BELAJAR MAHASISWA DALAM MATA KULIAH SENAM PRAKTEK - Indrayogi Indrayogi; Tatang Suryadin (Universitas Majalengka, 2018)
AbstractThe scientific approach is intended to provide understanding to students in knowing, understanding various materials using a scientific approach, that information can come from anywhere, at any time, not dependent on information in the direction of the teacher